Photographic narrative of the time of terrorism in peru: comparison of the photographic exhibition «yuyanapaq. To remember» with el diario de marka and caretas magazine. Cases uchuraccay and lucanamarca (1983) - Vallejo Moreno, Joaquín Antonio (2019)
This Scientific Article analyzes the different narratives that exist about the internal armed conflict, based on the creation of the archives archive, «Yuyanapaq. To remember» and comparing this file with the written media The Journal of Marka and the research magazine Caretas in a specific case: Uchuraccay. Journalistic photography, which at the time performed an informative task, makes the transition to documentary photography to leave a perennial imprint in social memory as an instrument of remembrance of the cruelty experienced in those twenty years of terrorism. These visual narratives reflect a fact that happened and that is historically proven to have happened but, nevertheless, the political or ideological position that is taken on this subject makes the final message to be manipulated at the convenience of both the media studied and the story which shows the State in the exhibition «Yuyanapaq. To remember».